ANALISIS PENGARUH MODAL DAN TENAGA KERJA KERJA TERHADAP PRODUKSI KELAPA SAWIT PADA PT. GRUTI LESTARI PRATAMA MEDAN - Rianto Rianto (Universitas Islam Negeri Sumatera Utara, 2015)
Needs of optimal capital and skilled labor plays an important role in carrying out the production process. Factors palm oil production is crucialn for manufacturers producing cooking oil, butter and other manufacturers mainly use raw materials from palm oil almost of the producers are located in the region of North Sumatra. The use of capital and labor effective and efficient will result in optimal production of palm oil. The use of capital and labor in the production process of palm oil at PT. Gruti Pratama Lestari significant effect on production. Economic indicators that affect the level of production is investment/capital, labor and technology advancement. Capital formation, the material in the form of machines, tools and equipment as well as improving the quality of human resources is seen as a major factor in the economic development that will lead to the full utilization of economic resources available. The use of more advanced technology will create efficiencies in production that ultimately result in increased production. PT. Gruti Pratama Lestari is one of the private plantations producing palm oil fresh fruit bunches (FFB) in North Sumatra. The presence of all these companies was instrumental in improving the region's economic growth, apart from an increase inrevenue (PAD) can also create new jobs for the society in general as well as surrounding communities in particular. To support the palm oil production process PT. Gruti Pratama Lestari in need of capital and labor. The results of the analysis of data with simultaneous test shows that capital and labor are very significant influence on the production of palm oil PT. Gruti Pratama Lestari at 95% confidence level. The results of the analysis with partial test shows that capital very significant influence on the production of palm oil, and labor have a significant effect on the production of palm oil at 95% confidence level. Judging from the use of factors of production to the production of capital turned out to be more dominant than labor. This means that the use of capital has more influence on the increase in palm oil production than labor. Standardized Coeffecients capital of .0915% and the Standardized Coeffecients work force by 0132 against the production of palm oil, a much greater capital than labor means that PT. Gruti Pratama Lestari using capital-intensive technology.